Istikhdām kitāb “Mumtāz” ka-kitāb ta‘līmī li-ta‘līm ‘ilm an-naḥw fī al-madrasah al-mutawassiṭah Insān Cendikia Mandirī fī Sīdoārjo - Al Fahrezy, Moh. Abdurrahman; Lailatul Qomariyah; Muhammad Dzikru Alfin Maulaya (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2025)
In this era, many schools in Indonesia recognize the importance of Arabic language, particularly Nahwu science. "Indusan Cendekia Mandiri Sidoarjo" school is one of the schools that offers Arabic language lessons to all its students, where Nahwu science is included in the curriculum for 8th-grade students. The "Mumtaz" book is used as a textbook to teach Nahwu science to 8th-grade students at "Indusan Cendekia Mandiri Sidoarjo" school. Based on this background, the problems discussed in this study are how the "Mumtaz" book is used as a textbook to teach Nahwu science at "Indusan Cendekia Mandiri Sidoarjo" school, as well as the advantages and disadvantages of the "Mumtaz" book as a textbook for teaching Nahwu science at "Indusan Cendekia Mandiri Sidoarjo" school. This study uses a qualitative descriptive method through field study with a qualitative descriptive approach. The data collection methods used include observation, interviews, and documentation. The data sources are primary data from participants: two teachers and 8th-grade students at "Indusan Cendekia Mandiri Sidoarjo" school. In general, the "Mumtaz" book is considered effective in facilitating students' understanding of Nahwu science through engaging teaching methods. However, to overcome the existing shortcomings, additional contextual explanations and practical examples are needed in this book. This study concludes that although the "Mumtaz" book has many advantages, further improvements are still needed to help students connect theory with practice more effectively. English Translation: In this era, many schools in Indonesia recognize the importance of the Arabic language, particularly Nahwu science. "Indusan Cendekia Mandiri Sidoarjo" school is one of the institutions that offers Arabic lessons to all its students, with Nahwu included in the 8th-grade curriculum. The "Mumtaz" textbook is utilized to teach Nahwu to these students. This study explores the use of the "Mumtaz" textbook in teaching Nahwu at "Indusan Cendekia Mandiri Sidoarjo" school, along with its advantages and disadvantages. Employing a qualitative descriptive method, the research gathers data through observation, interviews, and documentation from two teachers and 8th-grade students. The findings indicate that the "Mumtaz" textbook is effective in enhancing students' understanding of Nahwu through engaging methods. However, additional contextual explanations and practical examples are necessary to address its shortcomings. While the textbook has numerous benefits, further refinement is required to facilitate a more effective connection between theory and practice for students.